In Situ Determination of Sulfide Turnover Rates in a Meromictic Alpine Lake - Lüthy, Lucas (American Society for Microbiology, 2000)
A push-pull method, previously used in groundwater analyses, was successfully adapted for measuring sulfide turnover rates in situ at different depths in the meromictic Lake Cadagno. In the layer of phototrophic bacteria at about 12 m in depth net sulfide consumption was observed during the day, indicating active bacterial photosynthesis. During the night the sulfide turnover rates were positive, indicating a net sulfide production from the reduction of more-oxidized sulfur compounds. Because of lack of light, no photosynthesis takes place in the monimolimnion; thus, only sulfide formation is observed both during the day and the night. Sulfide turnover rates in the oxic mixolimnion were always positive as sulfide is spontaneously oxidized by oxygen and as the rates of sulfide oxidation depend on the oxygen concentrations present. Sulfide oxidation by chemolithotrophic bacteria may occur at the oxicline, but this cannot be distinguished from spontaneous chemical oxidation.